DEPTOR promotes bone marrow adipose tissue expansion in calorie restricted mice. - Arcedo, Jesús; Durán-Jimenez, Iván Jesús; Csukasi, Fabiana (My University, 2024)
Elevated levels of fat in bones is a characteristic feature of osteoporosis and other skeletal disorders. While the molecular mechanism behind this shift between bone and fat formation remains incompletely understood, it is evident that the alteration of skeletal stem cell (SSC) differentiation likely plays a pivotal role. In particular, cellular metabolism is critical for SSC maintenance and lineage allocation. Interestingly, both osteoporosis and dietary restrictions lead to similar increased fat/bone ratio. Recently, we showed high levels of DEPTOR, an mTOR inhibitor and therefore a metabolic regulator, in several skeletal dysplasias with altered differentiation of skeletal progenitors. Here, we elucidate the role of DEPTOR in the increase in bone marrow adipose tissue (BMAT) under restricted nutrition. WT mice subjected to a 30% caloric restriction showed decreased trabecular bone and increased BMAT whereas DEPTOR KO mice exhibited little to none BMAT increase and even higher trabecular bone parameters compared to WT in response to caloric restriction. Proteomic analysis from bone marrow revealed 1110 upregulated and 478 downregulated proteins under caloric restriction in WT mice. Interestingly, in calorie restricted DEPTOR KO mice, more than half of these proteins reverted to levels similar to those observed in WT controls. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that these proteins contribute to several processes related to lipids such as fatty acid biosynthesis, elongation, and metabolism. These results point to DEPTOR as a key regulator in the metabolic control of skeletal progenitors’ differentiation under specific nutritional status. They also provide the rationale for its study as a pathological marker of abnormal bone/fat balance and as a potential target for the treatment of different low bone mass pathologies.
Keywords: Osteogénesis; Células medulares; Tejido adiposo; Grasa (Fisiología); Dieta baja en calorías; DEPTOR; Osteogenesis; Adipogenesis; Skeletal stem cells; Caloric restriction; Bone marrow adipose tissue